JUMLAH TEMPAT PENELURAN PENYU HIJAU (Chelonia mydas) BERDASARKAN VEGETASI PANTAI DI TAMAN WISATA ALAM (TWA) TANJUNG BELIMBING KECAMATAN PALOH KABUPATEN SAMBAS - Kurniawan, Wawan; Erianto, Erianto; Dewantara, Iswan (Universitas Tanjungpura, 2020)
The decline in the population of green sea turtles (Chelonia mydas) occurs continuously due to the destruction of the nesting beach habitat, therefore efforts are needed to increase the green sea turtle population by rearranging nesting sites. One thing that is considered important from the green sea turtle nesting habitat is the coastal vegetation. This research was conducted in Tanjung Belimbing Nature Tourism Park, Sambas Regency, West Kalimantan Province. This study aims to obtain information on vegetation conditions that are preferred by green sea turtles to lay eggs through the number of nesting sites approach. The method used is a survey method. Data collection was carried out by direct observation in the field. In this study, 12 nesting sites were found spread over four observation sites, with the highest number of nesting site found at observation location 1 as many as 8 nesting sites. At observation location 1, besides cemara laut (Casuarina equisetifolia) and pandan laut (Pandanus tectorius) also found waru (Hibiscus tiliaceus) and api-api (Avicennia sp) as well as shrub plants such as kamboja laut (Scaevola taccada), serunai laut (Melanthera biflora) ) and herbal plants such as tapak kuda (Ipomoea pes-caprae), alaban tanah (Vitex rotundifolia), rumput tembaga (Ischaemum muticum), bayam berduri (Amaranthus sp) and bakung laut (Crynum asiaticum L).Keywords: Nesting Sites, Vegetation, Green sea turtle, Tanjung Belimbing Nature Tourism Park